Pengaruh Faktor Budaya dan Kepribadian terhadap Keputusan Pembelian - Jauhari, Tontowi; Evi Husniati Sya’idah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The decision to purchase a product or service is not an isolated act; it is the result of a long process influenced by various internal and external factors. The purpose of this study is to analyze the influence of culture and personality on purchasing decisions. This study employed a quantitative associative method, utilizing primary data, and a sample of 30 individuals. Data analysis was conducted using multiple regression. The results demonstrate that the cultural factor (X1) has a positive influence on purchasing decisions of 0.233, while the personality factor (X2) has a positive influence of 0.160. The coefficient of determination of 0.813 demonstrates that in addition to their independent influence, the cultural variable (X1) and personality variable (X2) also have a joint influence on purchasing decisions. These findings suggest that understanding consumer culture and personality is necessary for developing effective marketing strategies. Keywords: Culture, Personality, Consumer Behavior, Purchasing Decisions